Pengembangan Lembar Kerja Peserta Didik Berbasis Model Problem Based Learning untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik Kelas VII SMP - Anggriani, Friska; Khayroiyah, Siti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to determine the validity, practicality and effectiveness of Student Worksheets in improving the communication skills of class VII SMP students. The research used (Research and Development) uses a development model carried out by Thiagarajan, Semmel, & Semmel, where this model is referred to as the 4D model, namely define, design, develop and disseminate. Data collection techniques are through observation and interviews, questionnaires, learning outcomes tests. The results of this research show that: 1) the validity of the LKPD was obtained with an average score of 89.8%, within very valid criteria. And it can be concluded that the Problem Based Learning LKPD is suitable for use by students. 2) the practicality of LKPD obtained an average of 90%, which shows that LKPD is practical and provides a new atmosphere for students so that the use of LKPD is declared feasible. 3) effectiveness in terms of the effectiveness of students in following the research process using the problem based learning model and the results of research from the pretest and posttest conducted on students obtained an average score of 0.63 in the range 0.30≤(g)<0.75 with eligibility criteria "effective and moderate".